Blood metabolites reflect the effect of gut microbiota on differentiated thyroid cancer: a Mendelian randomization analysis - Zhang, Hanfei; Li, Yuhao; Li, Lin (BMC cancer, 2025)
Background Studies have linked gut microbiome and differentiated thyroid cancer (DTC). However, their causal relationships and potential mediating factors have not been well defined. Our study investigated the causal relationships between the gut microbiome, papillary thyroid cancer (PTC) and follicular thyroid cancer (FTC), as well as the mediating effect of potential blood metabolites, using genetic approaches. Methods Leveraging the summary statistics of gut microbial taxa, blood metabolites, PTC and FTC from the largest genome-wide association studies (GWAS) to date, we applied the bidirectional and mediation Mendelian randomization (MR) design. The multivariable MR approach based on Bayesian model averaging (MR-BMA) was used to prioritize the most likely causal taxa. Furthermore, metabolic pathway analysis was performed via the web-based Metaconflict 4.0. Results After sensitivity analyses, we identified 4 taxa, 19 blood metabolites, and 5 gut bacterial pathways were causally associated with PTC. Similarly, 3 taxa, 31 blood metabolites, and 3 gut bacterial pathways were found to be causally associated with FTC, with 2 blood metabolites exhibiting bidirectional causal relationships. Metabolic pathway analysis revealed 8 significant pathways in PTC and FTC. MR-BMA analysis pinpointed species Bifidobacterium longum as the primary causal taxon for PTC and genus Bacteroides for FTC. The mediation MR analysis showed that sphingomyelin (d18:2/23:0, d18:1/23:1, d17:1/24:1) and 2-hydroxysebacate mediated the causal effects of specific gut microbiota on PTC and FTC, respectively. Conclusion The study suggested a causal relationship between several gut microbial taxa and DTC, and that specific blood metabolites might mediate this relationship.